Romer's Hypothesis Validation and Threshold of Trade Openness in ASEAN - Anggit Hamidi; Alvin Sugeng Prasetyo (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2022)
ABSTRACTThe purpose of this study is to test and analyze Romer's hypothesis regarding the impact of trade openness on inflation. In addition, this study also aims to measure the threshold point of trade openness. The method used is the System GMM and the Threshold Panel for the period 2010-2021. The estimation results show that trade openness has a significant effect on inflation. The sign of the coefficient of trade openness is positive, meaning that an increase in trade openness will lead to higher inflation. These results mean that Romer's hypothesis is invalid in ASEAN. The government is expected to be able to reduce the degree of trade openness by re-establishing agreements with bilateral and multilateral countries. If the trade agreement is profitable then it is continued, if it is not profitable it is better not to continue.Keywords: Trade Openness, Inflation, System GMM, ASEAN